Pipistrellus kuhlii - Toffoli, Roberto; Culasso, Paola; Locatelli, Andrea G.; Giraudo, Luca (Zenodo, 2016)
Pipistrellus kuhlii (Kuhl, 1817) Risk Level Europe: Least Concern - LC (Temple & Terry, 2007). Italy: Least Concern - LC (Rondinini et al. , 2013). This species was detected several times up to 1450 m a.s.l., nearby the locality of Palanfrè (Vernante), where single males were also captured on 2 nd and 12 th August, 2006. A reproductive roost located in a roof was found in Entraque (850 m a.s.l.). Here 30 individuals and 42 individuals were respectively counted exiting the roost on 23 rd August, 1995 and on 12 th July, 2009. Published as part of Toffoli, Roberto, Culasso, Paola, Locatelli, Andrea G. & Giraudo, Luca, 2016, Bats of Alpi Marittime Nature Park (North West Italy) and Site of Community Importance IT 1160056: distribution and status, pp. 3-13 in Natural History Sciences 3 (1) on page 10, DOI:10.4081/nhs.2016.254, http://zenodo.org/record/12523731